Sentipensante (sensing/thinking) pedagogy : educating for wholeness, social justice and liberation - Rendón, Laura I. (Stylus Pub., 2009)
Laura Rendón reconnects readers with the original impulse that led them to become educators; and to help them rediscover, with her, their passion for teaching and learning in the service of others and for the well being of our society. She offers a transformative vision of education that emphasizes the harmonic, complementary relationship between the sentir of intuition and the inner life, and the pensar of intellectualism and the pursuit of scholarship; between teaching and learning; formal knowledge and wisdom; and between Western and non-Western ways of knowing.